Dampak Transformasi Era Digital Terhadap Manajemen Sumber Daya Manusia - Angga Wahyudi; Muhammad Bhismi Thoifurqoni Assyamiri; Wilda Al Aluf; Mohammad Ryan Fadhillah; Shinta Yolanda; M. Isa Anshori (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The digital era has changed the paradigm and practice of human resource management (HR). This article analyzes the impact of digital transformation on HR, with a focus on paradigm shifts, digital skills development, and the use of technology in decision making. The pre-digital era emphasized administration, while the digital era demands attention to employees' digital skills. Developing digital skills is important, considering these skills are key in the modern world of work. A competency-based approach is a more suitable method for dealing with technological change. HR management has a major role in facilitating organizational adaptation and success in the ever-evolving digital era. The World Economic Forum (2020) said skills such as understanding technology, data analysis, and proficiency in using digital devices have become important in today's world of work. In facing the digital era, organizations are faced with new challenges and opportunities. Changing the HR management paradigm from administrative to strategic requires adaptive and innovative leadership. Digital skills development is the foundation for productivity and competitiveness. Therefore, employee training and development must be the main focus. A competency-based approach allows a more precise identification of the required skills requirements. In addition, the use of technology and data analysis enables more accurate and objective decision making.